Doppler Positioning Performance of LEO Mega Constellation - Yulu ZHANG; Zhen LI; Chuang SHI; Guifei JING (天地一体化信息网络)
This paper proposed a Doppler-only point-solution algorithm and analyzed the Doppler positioning performance based on the Starlink constellation.The Doppler positioning accuracy was about 3～6 m.To achieve the meter-level positioning accuracy, the satellite position and velocity errors should be within several meters and several centimeters per second, respectively.The ionospheric delay rates of C-band signal would cause about 2 m error in Doppler positioning.The positioning error would increase by dozens of meters if there were no corrections for the tropospheric errors.To ensure convergence in the LEO-based Doppler positioning, the initial receiver position error should be less than 300 km when the satellites orbit at an altitude of 550 km.